Interdigital sensors progress over the last two decades - Mukhopadhyay, Subhas Chandra; George, Boby; Roy, Joyanta Kumar; Islam, Tarikul (Cham, Switzerland Springer, 2021)
The book highlights the research contributions of the interdigitated (IDT) sensors over a period of two decades in the field of sensing technology. It presents theory, design, and practical realization of the IDT sensors working over wide frequency rage for scientific, industrial, and consumer applications. The IDT sensors have been widely investigated for wide range of sensing applications including agriculture, environmental monitoring, structural health monitoring, health care, food and beverage testing, testing of dielectric material, proximity sensing, microfluidic application, automatic dispensing system etc. Hence, importance of IDT sensors is growing continuously for future applications. As such, it offers a key reference guide on IDT sensors for students, applied physicists, material scientists, engineers, sensors designers and technicians.
Electronic reproduction
Keywords: Intelligent sensors; Electronics -- Safety measures; Electronic books